Effect of Metformin and Clomiphene Citrate in Improving Fertility in Subfertile Women with Polycystic Ovary Syndrome: A Randomized Controlled Trial - Begum, Hasina; Chowdhury, TA; Begum, Ferdousi; Begum, Shamsun Nahar; Kabir, Nazneen; Haque, Md Abidul (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: The main aim of this study was to compare the effect of metformin and clomiphene citrate on ovulation and conception rate in PCOS patients. Methodology: This randomized controlled trial was undertaken in the infertility outpatient department in Institute of Child and Maternal Health (ICMH), Dhaka during the period from January 2012 to December 2012. Total 71 PCOS women based on Rotterdam criteria were selected after randomization. They were divided into two groups - Group I (n=35) received metformin 500mg per oral thrice daily and Group II (n= 36) received clomiphene citrate 100mg orally per day from D2 for five days up-to six months. Results: Baseline characteristics of both sample groups were almost similar. Ovulation was confirmed by measuring D21 serum progesterone. Cumulative ovulation rate over six months period was not statistically different (57.14 % and 61.11%); (P=0.115), and pregnancy rate was (34.28 % and 42.85%); (P=0.521)respectively. Conclusion: Metformin has been found to be as effective as clomiphene citrate in terms of ovulation (57.14 % and 61.11%); and pregnancy rate (34.28 % and 42.85%) respectively Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 15-20